PROFIT LOSS SHARING FINANCING IN INDONESIA ISLAMIC RURAL BANKS: AN EVALUATION AMIDST GLOBAL UNCERTAINTY - Muhammad Anis; Roisatun Kasanah; Ahmed R. Rashed (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2025)
Although the Islamic banking industry has been developing for more than three decades, profit-loss sharing (PLS) financing has yet to secure a significant share of the overall financing portfolio. Against this backdrop, this study focuses on Indonesia’s Islamic Rural Banks (IRBs), which play a crucial role in serving micro and small enterprises nationwide. A key challenge for these institutions is the rising global uncertainty, which heightens risks, complicates financing decisions, and may hinder the growth of PLS-based contracts. Using the Autoregressive Distributed Lag (ARDL) model, this study examines both the short-term dynamics and the long-term impacts of operational efficiency (BOPO), profitability (ROA), inflation rate, industrial production index (IPI), and the World Uncertainty Index on profit-loss sharing financing. The analysis employs monthly data spanning the period from 2011 to 2024. The findings indicate that a combination of bank-specific factors and macroeconomic conditions plays a critical role in shaping PLS financing decisions in the short term. However, in the long term, the sustainability of PLS financing is more strongly linked to overall economic growth. Conversely, global uncertainty does not exert a significant influence, suggesting that IRBs exhibit relative resilience to external shocks. It suggests that PLS financing is more closely associated with economic growth and specific banking conditions than with global uncertainty. This study provides several recommendations for IRBs to enhance the implementation and sustainability of PLS-based financing.